Do circular economy practices matter for financial growth? An empirical study in China. (10th October 2022) - Yu, Yubing; Xu, Jiawei; Zhang, Justin Zuopeng; Wu, Ye; Liao, Zhongju
Abstract: The aggravation of environmental pollution and resource depletion has urged the international community to seek viable solutions. As the damage caused by the manufacturing industry is particularly destructive to the environment, finding an effective governance model is imperative. This study draws upon the organizational capability view to investigate the impact of circular economy practices (ecological design and investment recovery) on financial performance through environmental and innovation performance. Using structural equation modeling analyzing the data from 308 manufacturers in China by AMOS 21.0 software, we find that ecological design and investment recovery can directly enhance companies' performance. Also, environmental and innovation performances mediate the positive effects of circular economy practices on financial performance. Meanwhile, implementing ecological design contributes to investment recovery. Our study identifies the new path of circular economy practices in promoting financial performance through environmental and innovation improvement. The findings also guide managers to effectively implement ecological design and investment recovery to maximize company benefits.